A unifying theory of aging and mortality - Valentin Flietner; Bernd Heidergott; Frank den Hollander; Ines Lindner; Azadeh Parvaneh; Holger Strulik (Tinbergen Institute, 2024)
In this paper, we advance the network theory of aging and mortality by developing a causal mathematical model for the mortality rate. First, we show that in large networks, where health deficits accumulate at nodes representing health indicators, the modeling of network evolution with Poisson processes is universal and can be derived from fundamental principles. Second, with the help of two simplifying approximations, which we refer to as mean-field assumption and homogeneity assumption, we provide an analytical derivation of Gompertz law under generic and biologically relevant conditions. We identify the parameters in Gompertz law as a function of the parameters driving the evolution of the network, and illustrate our computations with simulations and analytic approximations.
Keywords: I10; J10; 330; Sterblichkeit; Alternde Bevölkerung; Netzwerkökonomik; Gesundheit; Theorie